2023
DOI: 10.1007/s10571-023-01392-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hypothyroidism and Alzheimer’s Disease: A Tale of Two

Abstract: Hypothyroidism (HPT) HPT could be a risk factor for the development and progression of Alzheimer’s disease (AD). In addition, progressive neurodegeneration in AD may affect the metabolism of thyroid hormones (THs) in the brain causing local brain HPT. Hence, the present review aimed to clarify the potential association between HPT and AD. HPT promotes the progression of AD by inducing the production of amyloid beta (Aβ) and tau protein phosphorylation with the development of synaptic plasticity and memory dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Besides, oxidative stress and inflammation in different systemic diseases may reduce the function of the thyroid gland leading to PHT [ 38 ]. Interestingly, long-term PHT can affect the functions of the CNS and increase the risk for the development of Alzheimer's disease (AD) by triggering inflammation and oxidative stress which play a critical role in the pathogenesis of AD [ 39 ].…”
Section: Primary Hypothyroidismmentioning
confidence: 99%
“…Besides, oxidative stress and inflammation in different systemic diseases may reduce the function of the thyroid gland leading to PHT [ 38 ]. Interestingly, long-term PHT can affect the functions of the CNS and increase the risk for the development of Alzheimer's disease (AD) by triggering inflammation and oxidative stress which play a critical role in the pathogenesis of AD [ 39 ].…”
Section: Primary Hypothyroidismmentioning
confidence: 99%
“…AD neuropathology is developed due to extracellular accumulation of neurotoxic amyloid beta (Aβ) and intracellular deposition of hyperphosphorylated tau protein which form neurofibrillary tangles (NFTs). 53 , 54 It has been shown that the over‐activation of brain RAS is associated with the development of cognitive impairment and memory deficits. 55 It has been illustrated that overactivity of RAS in hypertensive patients triggers the development and progression of AD by activating of neuronal AT1R which induce oxidative stress and neuroinflammation.…”
Section: Role Of Brain Ras In Neurodegenerative Di...mentioning
confidence: 99%
“…AD is the commonest neurodegenerative disease in elderly and represents two third of all dementia cases. AD neuropathology is developed due to extracellular accumulation of neurotoxic amyloid beta (Aβ) and intracellular deposition of hyperphosphorylated tau protein which form neurofibrillary tangles (NFTs) 53,54 . It has been shown that the over‐activation of brain RAS is associated with the development of cognitive impairment and memory deficits 55 .…”
Section: Role Of Brain Ras In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Analysis of brain tissues of AD patients in a postmortem study revealed that the expression of thyroid hormone receptors was higher than controls [87]. Bavarsad et al [87] suggested that thyroid disorders, either hyperthyroidism or hypothyroidism, may be involved in the pathogenesis of AD as thyroid hormones affect memory and cognitive functions [88,89]. A prospective cross-sectional study of 69 patients showed that thyroid-stimulating hormone levels and thyroid hormones correlated with cerebral tau burden and cognitive dysfunction [88].…”
Section: Neuroserpin In Admentioning
confidence: 99%